Biomechanical report for the IAAF World Championships London 2017 high jump men's - Nicholson, G.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2018)
The men`s high jump final took place on the night of August 13th in good weather conditions. Approaching the event, the overriding favourite was Mutaz Essa Barshim with the Qatari remaining undefeated in his last six competitions and topping the outdoor season`s best list with a mark of 2.38 m. Despite favourable conditions, none of the finalists surpassed their season`s best. On the night, Barshim lived up to expectations surpassing his silver medal in the same stadium in 2012 and his disappointing fourth place finish in the last World Championships. The 26 year-old produced an impressive score card clearing 2.20 m, 2.25 m, 2.29 m, 2.32 m and 2.35 m. Despite holding the Asian record from 2014 with a mark of 2.43 m, Barshim was unable to raise the world lead to 2.40 m during his final attempts. Although it was Germany`s Mateusz Przybylko who had come closest to Barhsim`s world lead in 2017, it was Daniel Lysenko and Majd Eddin Ghazal who took silver and bronze respectively, with Lysenko competing through lingering pain caused by a recent injury to his take-off leg. (Attention! registration on the IAAF site is required for downloading)